2016
DOI: 10.22246/jikm.2016.37.6.1030
|View full text |Cite
|
Sign up to set email alerts
|

The Administration of Jeungmiyijin-tang to Rats with Induced Gastro Reflux Esophagitis

Abstract: Objectives: This study investigated the administration of Jeungmiyijin-tang (JYT) to rats with reflux esophagitis (RE) induced by pylorus and forestomach ligation operations. Methods: Twenty laboratory rats were divided into three groups with 5~7 rats in each group. The control group consisted of rats with no inflammation (CON). The RE group had rats with gastroesophageal reflux elicited by pylorus and forestomach ligation operations. The JYT group had rats that were orally administered Jeungmiyijin-tang (1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Notably, these 4 herbs are key components of Yijin-tang, a traditional herbal formula that has been used for centuries to address GERD and has demonstrated effectiveness in various animal models of GERD. [19,20] A previous study conducted in China also reported superior therapeutic outcomes for this herbal formula compared to omeprazole magnesium enteric-coated tablets in patients with GERD. [21] These findings align precisely with a previous review of Yijintang for GERD based on classical herbal literature.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, these 4 herbs are key components of Yijin-tang, a traditional herbal formula that has been used for centuries to address GERD and has demonstrated effectiveness in various animal models of GERD. [19,20] A previous study conducted in China also reported superior therapeutic outcomes for this herbal formula compared to omeprazole magnesium enteric-coated tablets in patients with GERD. [21] These findings align precisely with a previous review of Yijintang for GERD based on classical herbal literature.…”
Section: Discussionmentioning
confidence: 88%
“…The study’s findings suggested that this mechanism offers protection against reflux-induced mucosal damage. [ 20 ] In addition, another case study showed that Jeungmiyijin-tang plus Soojeom-san almost resolved a patient’s GERD symptoms. [ 34 ] Yukul-tang , in a rat experiment, demonstrated a significant reduction in the incidence of gastric ulcers compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning GERD and reflux esophagitis, there were studies on a variety of prescriptions and single or complex medications such as (597) Banhasasim-tang 13) , Yijin-tang 14,15) , Jwakum-whan 16) , Coptis Chinensis 17) , Artemisia Capillaris Herba 18) , Evodiae Fructus 19,20) , Citri Pericarpium 21) , and Ulmus Pumila Cortex 22) . However, there was no study comparing the therapeutic effect of Liriope platyphylla with PPI in studies related to GERD and reflux esophagitis.…”
Section: Liriope Platyphallamentioning
confidence: 99%